Meeting Targets in Competitive Product Markets - BISETTI, EMILIO; KAROLYI, STEPHEN A. (Journal of Finance, 2024)
ABSTRACT We show that public banks face negative stock return jumps after missing their earnings per share (EPS) targets, and theoretically and quantitatively link these jumps to bunching behavior in the EPS surprise distribution. Bunching banks cut deposit rates to meet their targets, but do so at the expense of deposit outflows and franchise value losses. Local competitors, including private banks unexposed to capital market pressure, increase deposit rates, compensating depositors for switching. Our results provide new evidence that performance targeting incentives can affect consumer product prices, and suggest that competition may provide a check on public firms' targeting efforts.